Prolonged neonatal jaundice: an audit of selective screening in community. (29th September 2015) - Cartledge, P; Kevlani, N; McClean, P
Abstract : Aims: Selective screening for neonatal liver disease by performing a split bilirubin test in any infant who remains jaundiced beyond two weeks of age has been recognised as good clinical practice. A community selective screening programme to case-find pathological prolonged jaundice has been in place in our city since December 2000. All infants with conjugated hyperbilirubinaemia (conjugated >20% of total bilirubin and >18 µmol/l), should be referred for investigation of liver disease. This audit looks at the efficiency of this programme. Methods: The authors identified all community screened infants from the biochemistry database. The Liver Unit database was also examined to find infants with liver disease, with the city postcode, who had not been selectively screened through this programme. Birth statistics were obtained from the city council. Results: According to the biochemistry database a total of 1154 samples were referred from the community between December 2000 and February 2008. 272 were excluded because of inadequate data, repeat sampling etc. Of the remaining 882 referrals, five had conjugated hyperbilirubinaemia. Three had significant pathology viz. biliary atresia, lipid storage disorder and idiopathic neonatal hepatitis. The remaining two had a borderline conjugated fraction which resolved on retesting. The Liver Unit database revealed a further 36 infants seen in the study period. 26 of these were referred by the neonatal unit. Nine infants were referred from the community outside the screening programme—four by community midwives (all aged ≤ 28 days) and five by general practitioners (only one ≤28 days). The final infant was identified as having Alagille's syndrome while attending clinic with her affected brother. She was not jaundiced. No infant with a negative screening test developed liver disease. The number of infants screened in the community increased each year. The incidence of neonatal liver disease was 1 in 1500 live births. Conclusion: Selective screening for neonatal liver disease had a sensitivity and negative predictive value of 100% for those infants who were tested. Ongoing education of community healthcare professionals is necessary to ensure all jaundiced infants are screened appropriately.